1996
DOI: 10.1111/j.1476-5381.1996.tb15755.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moderate hypoalbuminaemia on the renal metabolism and dynamics of furosemide in the rabbit

Abstract: 1 The present study aimed to investigate the influence of hypoalbuminaemia on the pharmacokinetics and pharmacodynamics of furosemide. Hypoalbuminaemia was produced by repeated plasmapheresis, to attain plasma albumin concentrations of 21.6+0.9 g 1', compared with 33.0+0.6 g 1' in controls (P<0.001). The per cent of bound furosemide in hypoalbuminaemic rabbits (90.8+0.7%) was lower than that in control rabbits (97.4+0.5%, P<0.001). The kinetics of intravenous furosemide (2.5 mg kg-') were studied in control (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
0
32
1
1
Order By: Relevance
“…By blocking the luminal K/Na/2Cl co-transporter type 2 in the thick ascending limb of the loop of Henle cells, furosemide may decrease the demand in supply/demand equation. Approximately 98% of furosemide bounds to plasma proteins and the GFR of the drug is very low 18,19. Hence, for exerting this effect, it is necessary that furosemide should be actively secreted from the proximal tubule via the organic anion transporter-1 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…By blocking the luminal K/Na/2Cl co-transporter type 2 in the thick ascending limb of the loop of Henle cells, furosemide may decrease the demand in supply/demand equation. Approximately 98% of furosemide bounds to plasma proteins and the GFR of the drug is very low 18,19. Hence, for exerting this effect, it is necessary that furosemide should be actively secreted from the proximal tubule via the organic anion transporter-1 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…In NS, levels of albumin and other plasma proteins are often extremely low, and the consequent increased volume of distribution decreases the amount delivered to the kidney [ 14 ]. Increasing the dose administered is the appropriate response to this; coadministration of albumin with diuretic has not been consistently demonstrated as being of additional benefi t [ 15 , 16 ].…”
Section: What Are the Pharmacokinetic Barriers To Achieving Therapeutmentioning
confidence: 99%
“…Animal studies demonstrate five mechanisms that could impair the responsiveness to loop diuretics in patients with the nephrotic syndrome, including 1) decreased delivery and/or decreased tubular secretion of the diuretic, 2) increased renal diuretic metabolism, 44 3) decreased blockade of the Na-K-2Cl cotransporter by the diuretic, 45 and 4) increased NaCl reabsorption by other nephron segments. Clinical studies confirm that nephrotic patients have an impaired tubular response to loop diuretics.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoalbuminemia decreases the binding of furosemide to plasma proteins and thereby increases its volume of distribution. 46 The secretion of loop diuretics by the proximal tubule is reduced by hypoalbuminemia, 44 and albumin infusion into nephrotic patients increases renal furosemide excretion in the urine. 47 Early work suggested that premixing furosemide with albumin prior to intravenous injection amplified diuresis, 48 but this was not confirmed by some others.…”
Section: Introductionmentioning
confidence: 99%